Adjusting teaching and learning strategies through formative assessment - Đặng Thị Diệu Hiền (Journal of Technical Education Science, 2014)
Assessment is the final stage of the teaching and learning process, but not the end stage of this process. It provides important information to improve teaching and learning. This article proposes some ideas about assessment process to adjust the surface learning strategies to depth learning strategies.